2020
DOI: 10.1111/jog.14548
|View full text |Cite
|
Sign up to set email alerts
|

lncRNA RHPN1‐AS1 promotes the progression of endometrial cancer through the activation of ERK/MAPK pathway

Abstract: Aim This study aimed to investigate the function of long noncoding RNA RHPN1 antisense RNA 1 (lncRNA RHPN1‐AS1) in the progression of endometrial cancer (EC) and its underlying molecular mechanisms. Methods The RHPN1‐AS1 expression was measured by quantitative reverse transcriptase‐polymerase chain reaction (qRT‐PCR) in EC tissues and cells. The cell clones, proliferation, cell cycle, apoptosis, migration and invasion in Ishikawa and HEC‐1A cells were respectively measured by colony formation assay, cell count… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…lncRNAs, which can serve as critical tumor promoters or suppressors, can affect the occurrence and progression of multiple types of diseases (23,24). HAGLROS is abnormally expressed in the serum of patients with pneumonia and it has been found to decrease apoptosis and autophagy in lipopolysaccharide-induced WI-38 cells (25).…”
Section: Discussionmentioning
confidence: 99%
“…lncRNAs, which can serve as critical tumor promoters or suppressors, can affect the occurrence and progression of multiple types of diseases (23,24). HAGLROS is abnormally expressed in the serum of patients with pneumonia and it has been found to decrease apoptosis and autophagy in lipopolysaccharide-induced WI-38 cells (25).…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we found that phosphorylation level of ERK, JNK and p38 was elevated by S100A7 overexpression and reduced by S100A7 silence. In EC, studies have demonstrated that the abnormally high expression of MAPK pathway-related proteins was clearly involved in the malignant progression and chemoresistance of EC [35,36]. Our finding suggested that S100A7 may activate ERK, JNK and p38 MAPK to accelerate EC progression.…”
Section: Discussionmentioning
confidence: 52%
“…The lncRNA RHPN1-AS1 was previously reported to be upregulated in various cancers and is frequently associated with cancer pathophysiology [ 6 , 10 , 47 ]. In OC, robust lncRNA RHPN1-AS1 expression was detected in cancer tissues; it serves as an unfavorable prognosticator and promotes tumor cell proliferation and metastasis [ 14 ] Our study showed that RHPN1-AS1 expression was enhanced in OC tissues and cells.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, targeting lncRNAs may interfere with cancer progression. Currently, RHPN1-AS1 is known to exhibit ceRNA activity against several antitumor miRNAs, such as miRNA-129, miR-625, miR-7-5p, and miR-485-5p, contributing to cancer tumorigenesis and progression [ 14 , 48–50 ]. Based on our bioinformatics prediction, we found that miR-485-5p is a novel target of RHPN1-AS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation